Śmierć. Między doświadczeniem a pojęciem - Iskra-Paczkowska, Agnieszka (Wydział Sztuki UR, 2017)
The article analyzes the issue of human finiteness. The reflection upon death runs in three perspectives: death as a generic phenomenon, death of a loved one (man as homo sepultor) and one’s own death. It includes issues like: the notion andexperience of death, self-knowledge in the prospect of death, the attitude towards death and its determinants, variability of the social and cultural attitude models towards death, the paradoxes of the term “death”. The ending presents the principles of contemporary thanatology, the study of “good life and good death ”.
Death. Between the concept and the experience of death
Keywords: śmierć; doświadczenie; wolność; skończoność; homo sepultor; tanatologia; nieśmiertelność; death; experience; freedom; finiteness; thanatology; immortality